Search for heavy neutrinos or third-generation leptoquarks in final states with two hadronically decaying τ leptons and two jets in proton-proton collisions at √s=13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (American Physical Society, 2017)
A search for new particles has been conducted using events with two high transverse momentum (pT) τ leptons that decay hadronically, at least two high-pT jets, and missing transverse energy from the τ lepton decays. The analysis is performed using data from proton-proton collisions, collected by the CMS experiment in 2015 at √ s = 13 TeV, corresponding to an integrated luminosity of 2.1 fb−1 . The results are interpreted in two physics models. The first model involves heavy right-handed neutrinos, N` (` = e, µ, τ ), and right-handed charged bosons, WR, arising in a left-right symmetric extension of the standard model. Masses of the WR boson below 2.35 (1.63) TeV are excluded at 95% confidence level, assuming the Nτ mass is 0.8 (0.2) times the mass of the WR boson and that only the Nτ flavor contributes to the WR decay width. In the second model, pair production of third-generation scalar leptoquarks that decay into τ τbb is considered. Third-generation scalar leptoquarks with masses below 740 GeV are excluded, assuming a 100% branching fraction for the leptoquark decay to a τ lepton and a bottom quark. This is the first search at hadron colliders for the third-generation Majorana neutrino, as well as the first search for third-generation leptoquarks in the final state with a pair of hadronically decaying τ leptons and jets.